The Semiotics of Penja in the Tabut Ritual: Shi‘a Influence and Local Culture in Bengkulu - Rahmat; Acep Iwan Saidi (Gorga : Jurnal Seni Rupa, 2025)
The presence and influence of Shi‘a Islam in Southeast Asia is a complex historical process shaped by peaceful cultural transmission rather than conflict. Arriving via Sufi networks, literature, and rituals from Persia and India, Shi‘a traditions harmoniously integrated with dominant Sunni-Syafi‘i practices. In Bengkulu, the Tabut ritual rooted in Shi‘a commemorations of Imam Husain’s martyrdom at Karbala was introduced in the early 18th century by Indian Shi‘a migrants from Madras and Bengal under British colonial rule. Central to the ritual is the Penja artifact, a five-fingered symbol representing the Khamsa or Panj-e-Tan, honoring the Prophet Muhammad, Ali, Fatimah, Hasan, and Husain. This emblem, along with miniature Zulfikar swords, embodies theological symbolism and communal identity. The Tabut festival, held annually from 1–10 Muharram, includes structured rites such as Mengambil Tanah, Duduk Penja, Menjara, and culminates in a grand Ashura procession. Parallels with Indian Shi‘a traditions especially in Awadh reveal the transnational nature of these symbols, which serve both commemorative and protective roles. The Khamsa’s integration into processions underscores its function as a mobile shrine and marker of solidarity, reflecting enduring connections between Southeast Asian Shi‘a practices and broader intellectual-religious networks across Iran, Iraq, and the Indian subcontinent.